Dielectric and electro-optical properties of a nematic liquid crystalline material with gold nanoparticles. Issue 12 (26th September 2018) - Elkhalgi, Hajer H. M.; Khandka, Sarita; Singh, U. B.; Pandey, K. L.; Dabrowski, R.; Dhar, Ravindra
ABSTRACT: We have prepared the composites of a room temperature nematic liquid crystalline material namely 4-(trans-4′-n-hexylcyclohexyl) isothiocyanatobenzoate (6CHBT) and gold nanoparticles (GNPs). Thermodynamic, electro-optical and dielectric properties have been investigated. Effect of dispersion of GNPs on various electro-optical and display parameters of host liquid crystalline material have been studied. Physical parameters such as threshold voltage, dielectric anisotropy and splay elastic constant have altered for composite systems. Due to the dispersion of GNPs, nematic to isotropic transition temperature is significantly increased. Relaxation frequency corresponding to flip-flop motion of the 6CHBT molecules about their short axes has increased due to the presence of GNPs. GRAPHICAL ABSTRACT: